Experiências de profissionais do Núcleo de Apoio à Saúde da Família na pandemia de covid-19 - Colombo, Emilio Augusto (2024)
The Family Health Support Center (NASF) are multidisciplinar teams responsible for expanding the actions of primary health care (PHC) in the public system, strengthening and qualifying the actions of the health care. During the covid-19 pandemic, there were several changes and reconfigurations, which transformed the ways of living and working of these professionals. Thus, a qualitative research was carried out to understand the experiences of the health professionals who make up the NASF teams, in a municipality in the interior of São Paulo, during the covid-19 pandemic. We sought to characterise the profile of these professionals and understand their controversies, strengths, challenges, confrontations, inventions and learnings. In this research, experience is understood as what happens to us and transforms us. For the construction of data were used: the researcher's field diary; questionnaire; twelve semi-structured interviews with narrative focus. The experiences were diverse among the professionals, presenting similarities and differences. The NASF was composed of social workers, physiotherapists, nutritionists, physical education professionals, psychologists and occupational therapists, most of whom remained throughout the pandemic. They were between 26 and 65 years old and professional time between 3 and 13 years. From the thematic analysis of content, four categories were formed: Work experiences at NASF pre-pandemic; Work process of the NASF during the pandemic: from discontinuity to inventions; Emotions and feelings of NASF workers during the pandemic; Overcoming difficulties and learnings. The results brought multifaceted experiences experienced by NASF professionals. They demonstrated the discontinuity of the work that was previously carried out, with changes that resulted in the breakdown of the longitudinality of care and relationships with the community and PHC teams. There was a lack of autonomy for NASF professionals to develop ways to combat the pandemic, which limited the scope of their actions. Furthermore, in this process of reorganizing the work process with the atomization of professionals, there was a distancing from the usual functions and attributes of the NASF, with the pandemic being an impetus for the tendency to mischaracterize PHC. Inventions emerged in health care, strengthening the interdisciplinary and uniprofessional role in areas previously unknown to them, such as management and telemonitoring. The experiences were described with different emotions and feelings, mainly the fear of becoming infected, of transmitting it to people close to them, as well as of not being competent to deal with the adversities of the pandemic, generating suffering. They built strategies to combat the pandemic in different ways, using different activities outside the work space to maintain mental health and at work they provided support among peers. The versatility of NASF professionals brought contributions to the management of the pandemic, regardless of the way they acted, whether developing specific actions within the professional core and/or actions in the health field that permeate all professionals. Through experiences, professionals reported that they were able to learn about their own health, interpersonal relationships and new professional responsibilities. Therefore, professionals contributed to care, with innovations, reconstructions, strengthening and qualifying health actions and allowing learning for professional performance as well as personal care.